2007
DOI: 10.1002/jrs.1882
|View full text |Cite
|
Sign up to set email alerts
|

Intermolecular H‐bond in propan‐2‐ol and its solutions with acetonitrile

Abstract: Formation of propan-2-ol-acetonitrile dimers is manifested in the Raman spectra as an appearance of a band of aggregates in the high-wavenumber side of the C N vibrational band of liquid acetonitrile (∼2 cm −1 ). The intensity of the band of aggregates changes with a change in the concentration of the mixture (1-0.05 mole fraction).For propan-2-ol we carried out nonempirical calculations of a structure of isolated dimer aggregates. The formation of an intramolecular H-bond between the H and the O atom of the H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 9 publications
(2 reference statements)
0
2
0
Order By: Relevance
“…Any complexity similar to that in the case of pyridine-propan-2-ol solutions [48] is not manifested for the 1040-cm −1 band of aggregates. In [49], it was shown that the participation of molecules of propan-2-ol in the formation of H-aggregates is evident not only in the band of O-H vibrations, but also in the bands of vibrations of atoms, which are not directly involved in the formation of intermolecular hydrogen bonds. In particular, the 820-cm −1 band of propan-2-ol involved in the formation of H-bonds in the process of self-association or with proton-donor molecules is appeared to be of doublet character.…”
Section: Results Of Experimental Studies and Calculationsmentioning
confidence: 99%
“…Any complexity similar to that in the case of pyridine-propan-2-ol solutions [48] is not manifested for the 1040-cm −1 band of aggregates. In [49], it was shown that the participation of molecules of propan-2-ol in the formation of H-aggregates is evident not only in the band of O-H vibrations, but also in the bands of vibrations of atoms, which are not directly involved in the formation of intermolecular hydrogen bonds. In particular, the 820-cm −1 band of propan-2-ol involved in the formation of H-bonds in the process of self-association or with proton-donor molecules is appeared to be of doublet character.…”
Section: Results Of Experimental Studies and Calculationsmentioning
confidence: 99%
“…152 This Raman study is of particular interest to the scientific community due to the biological importance of formamide and the general interest in donor-acceptor reactions which are central to a wide range of chemical activities. In a further work, Tukhvatullin et al 153 studied the intermolecular H-bond in propan-2-ol and its solutions with acetonitrile. Hydrogen bonding and motional narrowing in binary mixtures of 2-and 3-bromopyridine in methanol, probed by polarized Raman scattering and DFT calculations, were the subject of a work published by Ojha et al 154 The same research group 155 performed a concentration-dependent Raman study of the noncoincidence effect in the NH 2 bending and C O stretching modes of HCONH 2 in the binary mixture (HCONH 2 C CH 3 OH).…”
Section: Studies In Binary Mixtures Noncoincidence Effectmentioning
confidence: 99%